Trade and Capital Flows: Substitutes or Complements? An Empirical Investigation - Ansgar H. Belke; Clemens Domnick (Institute of Labor Economics (IZA), 2019)
This paper examines the linkages between the trade of goods and financial assets. Do both flows behave as complements (implying a positive correlation) or as substitutes (negative correlation)? Although a classic topic in international macroeconomics, the empirical evidence has remained relatively scarce so far, in particular for the Euro area where trade and financial imbalance played a prominent role in the build-up of the European sovereign debt crisis. Consequentially, we use a novel dataset, providing estimates for financial flows and its four main categories for 42 countries and covering the period from 2002-2012, to test the so-called trade-finance nexus. Since theoretical models stress that both flows might be influencing each other simultaneously, we introduce a novel time-varying instrumental variable based on capital control restrictions to estimate a causal effect. The results of the gravity regressions support theories that underline the complementarity between exports and capital flows. When testing the trade-finance nexus for different types of capital flows, the estimated coefficient is most pronounced for foreign direct investment, in line with theories stressing informational frictions. Robustness checks in the form of different estimation methods, alternative proxies for capital flows and sample splits confirm the positive relationship. Interestingly, the trade-finance nexus does not differ among countries belonging to the EMU, the European Union or among core and peripheral Euro area countries.
Keywords: F14; F15; F21; F41; 330; capital flows; economic integration; Heckscher-Ohlin paradigm; interaction between trade integration and capital mobility; trade